Conserved and Unique Functions of Blimp1 in Immune Cells - Nadeau, Samantha; Martins, Gislâine A. (Frontiers in Immunology, 2022)
B-lymphocyte-induced maturation protein-1 (Blimp1), is an evolutionarily conserved transcriptional regulator originally described as a repressor of gene transcription. Blimp1 crucially regulates embryonic development and terminal differentiation in numerous cell lineages, including immune cells. Initial investigations of Blimp1’s role in immunity established its non-redundant role in lymphocytic terminal effector differentiation and function. In B cells, Blimp1 drives plasmablast formation and antibody secretion, whereas in T cells, Blimp1 regulates functional differentiation, including cytokine gene expression. These studies established Blimp1 as an essential transcriptional regulator that promotes efficient and controlled adaptive immunity. Recent studies have also demonstrated important roles for Blimp1 in innate immune cells, specifically myeloid cells, and Blimp1 has been established as an intrinsic regulator of dendritic cell maturation and T cell priming. Emerging studies have determined both conserved and unique functions of Blimp1 in different immune cell subsets, including the unique direct activation of the igh gene transcription in B cells and a conserved antagonism with BCL6 in B cells, T cells, and myeloid cells. Moreover, polymorphisms associated with the gene encoding Blimp1 (PRDM1) have been linked to numerous chronic inflammatory conditions in humans. Blimp1 has been shown to regulate target gene expression by either competing with other transcription factors for binding to the target loci, and/or by recruiting various chromatin-modifying co-factors that promote suppressive chromatin structure, such as histone de-acetylases and methyl-transferases. Further, Blimp1 function has been shown to be essentially dose and context-dependent, which adds to Blimp1’s versatility as a regulator of gene expression. Here, we review Blimp1’s complex roles in immunity and highlight specific gaps in the understanding of the biology of this transcriptional regulator, with a major focus on aspects that could foster the description and understanding of novel pathways regulated by Blimp1 in the immune system.